2018
DOI: 10.1108/ijchm-07-2017-0461
|View full text |Cite
|
Sign up to set email alerts
|

Business intelligence and big data in hospitality and tourism: a systematic literature review

Abstract: Purpose-This study examines the extent to which Business Intelligence and Big Data feature within academic research in hospitality and tourism published until 2016, by identifying research gaps and future developments and designing an agenda for future research. Design/methodology/approach-The study consists of a systematic quantitative literature review of academic articles indexed on the Scopus and Web of Science databases. The articles were reviewed based on the following features: research topic; conceptua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
281
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(297 citation statements)
references
References 114 publications
4
281
0
12
Order By: Relevance
“…In a systematic review of literature from the Web of Science and Scopus published between 2000 and 2016, the authors selected 96 articles on big data and tourism, only 17 of which appeared in journals addressing hospitality or tourism [42]. In a similar review of literature from the Web of Science, ScienceDirect, SAGE Journals Online, Emerald Insight, Wiley Online Library and Springer published between 2007 and 2016, the authors examined 144 journal papers and 21 conference papers [41].…”
Section: Use Of Big Data Analytics In Hospitality and Tourism Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review of literature from the Web of Science and Scopus published between 2000 and 2016, the authors selected 96 articles on big data and tourism, only 17 of which appeared in journals addressing hospitality or tourism [42]. In a similar review of literature from the Web of Science, ScienceDirect, SAGE Journals Online, Emerald Insight, Wiley Online Library and Springer published between 2007 and 2016, the authors examined 144 journal papers and 21 conference papers [41].…”
Section: Use Of Big Data Analytics In Hospitality and Tourism Researchmentioning
confidence: 99%
“…gave rise to the link between their analysis and that of big data [34][35][36]. Therefore, much research has been devoted to social media analytics in general [37][38][39] and tourism analytics in particular [40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…In the tourism industry, the widespread availability of big data opportunities has changed the traditional research approach substantially. The enormous amount of available data has made the information extraction phase more complex, such that it now requires advanced analytics techniques to perform [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Differences were also found in the methodology and interpretation of research data. Mariani et al (2018) analyzing large data found that the academic research was fragmented in scope with limited methodologies and several gaps. A conceptual framework related to business domain and identification of critical business intelligence using big data was found to be missing in hospitality management research.…”
Section: Introductionmentioning
confidence: 99%